An Update on Advancement in Genomics Resources for Spiny Lobster Aquaculture Development - Courtney Lewis; Ahmad Farhadi; Susan Glendinning; Thomas Banks; Tara Kelly; Andrew G. Jeffs; Sandra Infante Villamil; John Breen; Jennifer M. Cobcroft; Arya Vazirzadeh; Basseer M. Codabaccus; Chris G. Carter; et al. (Reviews in Aquaculture, 2026)
The rapid advancement of high‐throughput sequencing technologies has transformed aquaculture genomics, enabling unprecedented insights into the biology and improvement of non‐model aquatic species. Among crustaceans, lobsters represent one of the most commercially valuable yet genomically underexplored taxa. This review synthesises the current state of genomic and transcriptomic resources available for spiny and slipper lobsters (Achelata), contextualising these within the broader decapod framework. We outline key genomic assemblies, transcriptomic atlases, and molecular tools that underpin emerging research on reproduction, nutrition, growth, stress tolerance, and disease resistance. We further highlight how omics‐driven approaches—spanning whole‐genome sequencing, SNP discovery, RNA interference, and nutrigenomics—are reshaping opportunities for selective breeding, reproductive control, and feed optimisation. Recent progress in establishing closed‐cycle aquaculture of Panulirus ornatus now provides the foundation for applying these molecular resources to address key production bottlenecks, including larval duration, cannibalism, and asynchronous moulting. We propose future directions integrating genomics, transcriptomics, and functional tools to accelerate sustainable domestication and genetic improvement of lobsters. Together, these advances mark a pivotal shift toward genomically informed spiny lobster aquaculture.

Differences in PFAS exposure between Pacific pinnipeds: The Galapagos (Zalophus wollebaeki) and California (Zalophus californianus) sea lions - Ashley E. Cave; Isabella G. Livingston; Taylor M. Gregory; Eleanor C. Hawkins; Shelly Vaden; Marjorie Riofrío-Lazo; Diane Deresienski; Gregory A. Lewbart; Anthony J. Orr; Emily Griffith; Christopher Fuller; Mark J. Strynar; et al. (Marine Pollution Bulletin, 2026)

NCBI Orthologs: Public Resource and Scalable Method for Computing High-Precision Orthologs Across Eukaryotic Genomes - Dong-Ha Oh; Alexander Astashyn; Barbara Robbertse; Nuala A. O’leary; W. Ray Anderson; Laurie Breen; Eric Cox; Olga Ermolaeva; Robert Falk; Vichet Hem; J. Bradley Holmes; Patrick Masterson; et al. (Journal of Molecular Evolution, 2025)
Orthologs are fundamental for enabling comparative genomics analyses that further our understanding of eukaryotic biology. The unprecedented increase in the availability of high-quality eukaryotic genomes necessitates scalable and accurate methods for orthology inference. The National Center for Biotechnology Information (NCBI) developed “NCBI Orthologs”, a resource and a computational pipeline designed to meet this challenge within the NCBI RefSeq framework. This system integrates protein similarity, nucleotide alignment, and microsynteny to achieve high-precision ortholog assignments across diverse eukaryotes. The pipeline leverages high-quality RefSeq annotations and processes genomes individually, ensuring scalability. Resulting ortholog data, organized into gene-level anchored sets, enables propagation of functional annotation information and facilitates comparative genomics. Critically, these data are integrated into the NCBI Gene resource, providing users with access from various entry points. The NCBI Datasets resource provides an intuitive interface to explore orthologous relationships on the web and allows bulk data download via the web, command-line tools, and an API. We detail the methodology, including anchor species selection and the decision tree used to arrive at high-confidence one-to-one orthology relationships. NCBI Orthologs is a valuable resource for facilitating functional annotation efforts and enhancing our understanding of eukaryotic gene evolution.

Increased quadriceps intermuscular adipose tissue in chronic liver disease is associated with an altered muscle transcriptome compared with healthy age matched controls - J. I. Quinlan; T. Nicholson; C. Bell; A. Dhaliwal; F. R. Williams; S. L. Allen; S. Choudhary; A. V. Rowlands; A. M. Elsharkawy; M. J. Armstrong; C. A. Greig; J. M. Lord; et al. (GeroScience, 2025)
Muscle fat infiltration (i.e., myosteatosis) is an important index of muscle health and pathology in disease states, such as chronic liver disease (CLD). However, it is unknown whether myosteatosis differs due to anatomical location. Further, the mechanistic implications of divergent intermuscular adipose tissue (IMAT) deposition remain unknown in patients with CLD. Thirty-three patients with CLD (55.0 ± 10.5 years) and 17 healthy controls (HC) (49.6 ± 15.4 years) were recruited. Quadriceps IMAT was estimated between 20 and 80% of muscle length and psoas IMAT at L3 via MRI. Body composition, muscle strength, and habitual activity were assessed. Fasted vastus lateralis muscle biopsies were collected and subjected to RNA sequencing analysis. ClinicalTrials.gov identifier: NCT04734496. IMAT was greater in CLD compared with HC in both quadriceps and psoas ( P < 0.0001). Quadriceps IMAT positively correlated with BMI ( r = 0.62), body fat ( r = 0.65), age ( r = 0.36), and negatively correlated with maximal knee extensor strength ( r = −0.45) and habitual physical activity ( r = −0.50) in CLD and HC. One hundred sixty-nine differentially expressed genes (DEGs) were identified in low IMAT CLD vs. HC, and 178 DEGs were identified in high IMAT CLD vs. HC. CLD patients with high and low IMAT exhibited defined expression profiles, with only 39 DEGs (representing 12.7%) in common. Pathway analysis of DEGs revealed enrichment of atrophic and pro-inflammatory pathways in the high IMAT group. IMAT is greater in patients with CLD compared to HC, irrespective of anatomical location, and is associated with reductions in muscle function and may be exacerbated by physical inactivity. IMAT appears to alter the muscle transcriptome in COLD, potentially exacerbating muscle loss. Graphical Abstract

A modeling framework to meta-analyse discard survival experiments illustrated by Nephrops norvegicus in European demersal trawl fisheries - M. Morfin; E. Savina; H.P. Benoît; M. Teixeira Alves; A. Albalat; T. Catchpole; C. Fox; M. McHugh; S. Méhault; H. Nilsson; M. Oliver; D. Valentinsson; et al. (Fisheries Research, 2025)

The role of nutrition in virus dynamics in vector-borne viral infections - Nora Heitzman-Breen; Jacob Golden; Yuyao Wang; James Weger-Lucarelli; Stanca M. Ciupe (Journal of Theoretical Biology, 2025)

An mTOR inhibitor discovery system using drug-sensitized yeast - Anna K. Breen; Sarah Thomas; David Beckett; Matthew Agsalud; Graham Gingras; Judd Williams; Brian M. Wasko (GeroScience, 2025)
Inhibition of the target of rapamycin (TOR/mTOR) protein kinase by the drug rapamycin extends lifespan and health span across diverse species. However, rapamycin has potential off-target and side effects that warrant the discovery of additional TOR inhibitors. TOR was initially discovered in Saccharomyces cerevisiae (yeast) which contains two TOR paralogs, TOR1 and TOR2 . Yeast lacking functional Tor1 are viable but are hypersensitive to growth inhibition by TORC1 inhibitors, which is a property of yeast that can be exploited to identify TOR inhibitors. Additionally, yeast lacking FK506-sensitive proline rotamase ( FPR1 ) or containing a tor1-1 allele (a mutation in the Fpr1-rapamycin binding domain of Tor1) are robustly and selectively resistant to rapamycin and analogs that allosterically inhibit TOR activity via an FPR1 -dependent mechanism. To facilitate the identification of TOR inhibitors, we generated a panel of yeast strains with mutations in TOR pathway genes combined with the removal of 12 additional genes involved in drug efflux. This creates a drug-sensitive strain background that can sensitively and effectively identify TOR inhibitors. In a wild-type yeast strain background, 25 µM of Torin1 and 100 µM of GSK2126458 (omipalisib) are necessary to observe TOR1 -dependent growth inhibition by these known TOR inhibitors. In contrast, 100 nM Torin1 and 500 nM GSK2126458 (omipalisib) are sufficient to identify TOR1- dependent growth inhibition in the drug-sensitized background. This represents a 200-fold and 250-fold increase in detection sensitivity for Torin1 and GSK2126458, respectively. Additionally, for the TOR inhibitor AZD8055, the drug-sensitive system resolves that the compound results in TOR1- dependent growth sensitivity at 100 µM, whereas no growth inhibition is observed in a wild-type yeast strain background. Our platform also identifies the caffeine analog aminophylline as a TOR1 -dependent growth inhibitor via selective tor1 growth sensitivity. We also tested nebivolol, isoliquiritigenin, canagliflozin, withaferin A, ganoderic acid A, and taurine and found no evidence for TOR inhibition using our yeast growth-based model. Our results demonstrate that this system is highly effective at identifying compounds that inhibit the TOR pathway. It offers a rapid, cost-efficient, and sensitive tool for drug discovery, with the potential to expedite the identification of new TOR inhibitors that could serve as geroprotective and/or anti-cancer agents.

Guidelines for Evaluating Artificial Light to Mitigate Unwanted Fisheries Bycatch - Noëlle Yochum; Junita D. Karlsen; Jesse F. Senko; John H. Wang; Valentina Melli; Michele Luca Geraci; Anne Christine Utne-Palm; Michael Breen; Elsa Cuende; Shannon M. Bayse; Jasmine Somerville; Andreas Hermann; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

Bioeconomic and sustainability performance of dairy-beef steer and heifer production systems differing in stocking rate - M. Kearney; E.G. O'Riordan; M. McGee; J. Breen; R. Dunne; P. French; P. Crosson (Livestock Science, 2024)

Mitigation of greenhouse gas emissions in pasture-based dairy-beef production systems - M. Kearney; E.G. O'Riordan; N. Byrne; J. Breen; P. Crosson (Agricultural Systems, 2023)

S15-01: Modelling kinetics and dynamics of chemicals at the US-EPA using the httk open-source platform - J. Wambaugh; S. Davidson-Fritz; A. Meade; M. Breen; R. Sayre; T. Wall; E. Kenyon; M. Evans; B. Wetmore; C. Ring (Toxicology Letters, 2023)

A holistic and comprehensive data approach validates the distribution of the critically endangered flapper skate ( Dipturus intermedius ) - Amy Garbett; Sophie L. Loca; Thomas Barreau; Manuel Biscoito; Caroline Bradley; Joe Breen; Maurice Clarke; Jim R. Ellis; Andrew M. Griffiths; Gary Hannon; Klara Jakobsdóttir; Claudia Junge; et al. (Journal of Fish Biology, 2023)
Morphological similarities between skates of the genus Dipturus in the north‐eastern Atlantic and Mediterranean have resulted in longstanding confusion, misidentification and misreporting. Current evidence indicates that the common skate is best explained as two species, the flapper skate ( Dipturus intermedius ) and the common blue skate ( D. batis ). However, some management and conservation initiatives developed prior to the separation continue to refer to common skate (as ‘ D. batis’ ). This taxonomic uncertainty can lead to errors in estimating population viability, distribution range, and impact on fisheries management and conservation status. Here, we demonstrate how a concerted taxonomic approach, using molecular data and a combination of survey, angler and fisheries data, in addition to expert witness statements, can be used to build a higher resolution picture of the current distribution of D. intermedius . Collated data indicate that flapper skate has a more constrained distribution compared to the perceived distribution of the ‘common skate’, with most observations recorded from Norway and the western and northern seaboards of Ireland and Scotland, with occasional specimens from Portugal and the Azores. Overall, the revised spatial distribution of D. intermedius has significantly reduced the extant range of the species, indicating a possibly fragmented distribution range.

Initial impacts of the COVID-19 pandemic on Australian fisheries production, research organisations and assessment: shocks, responses and implications for decision support and resilience - Emily M. Ogier; David C. Smith; Sian Breen; Caleb Gardner; Daniel J. Gaughan; Harry K. Gorfine; Alistair J. Hobday; Natalie Moltschaniwskyj; Ryan Murphy; Thor Saunders; Mike Steer; James Woodhams (Reviews in Fish Biology and Fisheries, 2023)
Australia’s fisheries have experience in responding individually to specific shocks to stock levels (for example, marine heatwaves, floods) and markets (for example, global financial crisis, food safety access barriers). The COVID-19 pandemic was, however, novel in triggering a series of systemic shocks and disruptions to the activities and operating conditions for all Australia’s commercial fisheries sectors including those of the research agencies that provide the information needed for their sustainable management. While these disruptions have a single root cause—the public health impacts and containment responses to the COVID-19 pandemic—their transmission and effects have been varied. We examine both the impacts on Australian fisheries triggered by measures introduced by governments both internationally and domestically in response to the COVID-19 pandemic outbreak, and the countermeasures introduced to support continuity in fisheries and aquaculture production and supply chains. Impacts on fisheries production are identified by comparing annual and monthly catch data for Australia’s commercial fisheries in 2020 with averages for the last 4–5 years. We combine this with a survey of the short-term disruption to and impacts on research organisations engaged in fisheries monitoring and assessment and the adaptive measures they deployed. The dominant impact identified was triggered by containment measures both within Australia and in export receiving countries which led to loss of export markets and domestic dine-in markets for live or fresh seafood. The most heavily impact fisheries included lobster and abalone (exported live) and specific finfishes (exported fresh or sold live domestically), which experienced short-term reductions in both production and price. At the same time, improved prices and demand for seafood sold into domestic retail channels were observed. The impacts observed were both a function of the disruptions due to the COVID-19 pandemic and the countermeasures and support programs introduced by various national and state-level governments across Australia to at least partly mitigate negative impacts on harvesting activities and supply chains. These included protecting fisheries activities from specific restrictive COVID-19 containment measures, pro-actively re-establishing freight links, supporting quota roll-overs, and introducing wage and businesses support packages. Fisheries research organisations were impacted to various degrees, largely determined by the extent to which their field monitoring activities were protected from specific restrictive COVID-19 containment measures by their state-level governments. Responses of these organisations included reducing fisheries dependent and independent data collection as required while developing strategies to continue to provide assessment services, including opportunistic innovations to harvest data from new data sources. Observed short run impacts of the COVID-19 pandemic outbreak has emphasised both the vulnerability of fisheries dependent on export markets, live or fresh markets, and long supply chains and the resilience of fisheries research programs. We suggest that further and more comprehensive analysis over a longer time period of the long-run impacts of subsequent waves of variants, extended pandemic containment measures, autonomous and planned adaptive responses would be beneficial for the development of more effective counter measures for when the next major external shock affects Australian fisheries.

Remission of insomnia in older adults treated with cognitive behavioral therapy for insomnia (CBT-I) reduces p16INK4a gene expression in peripheral blood: secondary outcome analysis from a randomized clinical trial - Judith E. Carroll; Richard Olmstead; Steve W. Cole; Elizabeth C. Breen; Jesusa M. Arevalo; Michael R. Irwin (GeroScience, 2023)
Late life insomnia may increase risk for accelerated biological aging. Intervening to treat insomnia may provide protection from biological aging by reducing the prevalence of senescent cells in the immune system, as indicated by gene expression of a marker of cellular senescence, p16 INK4a . In the present study, we determine whether treatment of insomnia in older adults with cognitive behavioral therapy for insomnia (CBT-I) would reduce p16 INK4a gene expression in peripheral blood mononuclear cells (PBMC), compared to a sleep education therapy (SET), an active comparator condition. Secondly, we investigate the relationship between sustained insomnia remission and reduced expression of p16 INK4a . Participants 60 + years old with insomnia were enrolled in a randomized controlled trial and assigned to CBT-I or SET. Analyses of 231 older adults (CBT-I = 119; SET = 112) examine baseline, post (2 months), and 24 months gene expression of p16 INK4a . Compared to baseline, expression of p16 INK4a increased in the SET group over 24 months ( P = 0.03), but showed no change in the CBT-I group. Those who received CBT-I and experienced sustained remission of insomnia had a significant decline in p16 INK4a expression by 24 months compared to baseline ( P = 0.02). Individuals not sustaining remission of insomnia exhibited overall increase expression of p16 INK4a by 24 months ( P = 0.03). In older adults with insomnia, p16 INK4a increases over 24 months, while CBT-I treatment of insomnia mitigates the increase in p16 INK4a . Further, sustained remission of insomnia using CBT-I leads to a decrease in p16 INK4a . These results suggest that behavioral interventions that are effective at treating insomnia might reduce the population of senescent cells in circulating blood.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

Atlantic mackerel ( Scomber scombrus ) change skin colour in response to crowding stress - Guro M. Tveit; Neil Anders; Morten S. Bondø; John R. Mathiassen; Mike Breen (Journal of Fish Biology, 2022)
Wild capture can be stressful for fish. Stress has the potential to induce mortality in released unwanted catches or negative flesh quality consequences in retained ones. Such effects compromise sustainable natural resource management and industry profitability. Mitigating stress during capture is therefore desirable. Biological indicators of stress can objectively inform fishers as to the functional welfare status of catches during fishing operations. If they are to be of practical use in mitigating stress during wild capture events, such indicators must be quantifiable, respond rapidly, reflect the level of induced stress and be easily observable. Atlantic mackerel ( Scomber scombrus ) are extensively targeted by purse seine fisheries in European waters but are particularly vulnerable to stress. Excessive crowding in the net is thought to be the principal stress mechanism. There is therefore a need to develop indicators of crowding stress for this species so that catch welfare can be improved. Here, we demonstrate that S. scombrus exhibit a skin colour change from predominately green to predominately blue when exposed to crowding stress. In sea cage trials, we induced various degrees of stress in groups of wild‐caught S. scombrus by manipulating crowding density and its duration. Skin colour was quantified in air using digital photography. The colour change occurred rapidly (within the typical duration of crowding events in the fishery), and its magnitude was correlated to the severity and duration of crowding. Bluer fish were also associated with higher levels of plasma lactate. No appreciable colour change was observed in uncrowded (control) groups during the treatment period. Nonetheless, unstressed S. scombrus did turn blue S. scombrus and could therefore be used to improve welfare during wild capture fishing.

Phototactic tails: Evolution and molecular basis of a novel sensory trait in sea snakes - Jenna M. Crowe‐Riddell; Bruno F. Simões; Julian C. Partridge; David M. Hunt; Steven Delean; Julian G. Schwerdt; James Breen; Alastair Ludington; David J. Gower; Kate L. Sanders (Molecular Ecology, 2019)
Dermal phototaxis has been reported in a few aquatic vertebrate lineages spanning fish, amphibians and reptiles. These taxa respond to light on the skin of their elongate hind‐bodies and tails by withdrawing under cover to avoid detection by predators. Here, we investigated tail phototaxis in sea snakes (Hydrophiinae), the only reptiles reported to exhibit this sensory behaviour. We conducted behavioural tests in 17 wild‐caught sea snakes of eight species by illuminating the dorsal surface of the tail and midbody skin using cold white, violet, blue, green and red light. Our results confirmed phototactic tail withdrawal in the previously studied Aipysurus laevis , revealed this trait for the first time in A. duboisii and A. tenuis , and suggested that tail photoreceptors have peak spectral sensitivities between blue and green light (457–514 nm). Based on these results, and an absence of photoresponses in five Aipysurus and Hydrophis species, we tentatively infer that tail phototaxis evolved in the ancestor of a clade of six Aipysurus species (comprising 10% of all sea snakes). Quantifying tail damage, we found that the probability of sustaining tail injuries was not influenced by tail phototactic ability in snakes. Gene profiling showed that transcriptomes of both tail skin and body skin lacked visual opsins but contained melanopsin ( opn4x ) in addition to key genes of the retinal regeneration and phototransduction cascades. This work suggests that a nonvisual photoreceptor (e.g., Gq rhabdomeric) signalling pathway underlies tail phototaxis, and provides candidate gene targets for future studies of this unusual sensory innovation in reptiles.

A novel canine kidney cell line model for the evaluation of neoplastic development: karyotype evolution associated with spontaneous immortalization and tumorigenicity - R. Omeir; R. Thomas; B. Teferedegne; C. Williams; G. Foseh; J. Macauley; L. Brinster; J. Beren; K. Peden; M. Breen; A. M. Lewis (Chromosome Research, 2015)

Canine urothelial carcinoma: genomically aberrant and comparatively relevant - S. G. Shapiro; S. Raghunath; C. Williams; A. A. Motsinger-Reif; J. M. Cullen; T. Liu; D. Albertson; M. Ruvolo; A. Bergstrom Lucas; J. Jin; D. W. Knapp; J. D. Schiffman; et al. (Chromosome Research, 2015)

Genomics in a changing arctic: critical questions await the molecular ecologist - Stan D. Wullschleger; Amy L. Breen; Colleen M. Iversen; Matthew S. Olson; Torgny Näsholm; Ulrika Ganeteg; Matthew D. Wallenstein; David J. Weston (Molecular Ecology, 2015)
Molecular ecology is poised to tackle a host of interesting questions in the coming years. The Arctic provides a unique and rapidly changing environment with a suite of emerging research needs that can be addressed through genetics and genomics. Here we highlight recent research on boreal and tundra ecosystems and put forth a series of questions related to plant and microbial responses to climate change that can benefit from technologies and analytical approaches contained within the molecular ecologist's toolbox. These questions include understanding (i) the mechanisms of plant acquisition and uptake of N in cold soils, (ii) how these processes are mediated by root traits, (iii) the role played by the plant microbiome in cycling C and nutrients within high‐latitude ecosystems and (iv) plant adaptation to extreme Arctic climates. We highlight how contributions can be made in these areas through studies that target model and nonmodel organisms and emphasize that the sequencing of the Populus and Salix genomes provides a valuable resource for scientific discoveries related to the plant microbiome and plant adaptation in the Arctic. Moreover, there exists an exciting role to play in model development, including incorporating genetic and evolutionary knowledge into ecosystem and Earth System Models. In this regard, the molecular ecologist provides a valuable perspective on plant genetics as a driver for community biodiversity, and how ecological and evolutionary forces govern community dynamics in a rapidly changing climate.

Genetic risk score analysis indicates migraine with and without comorbid depression are genetically different disorders - Lannie Ligthart; Jouke-Jan Hottenga; Cathryn M. Lewis; Anne E. Farmer; Ian W. Craig; Gerome Breen; Gonneke Willemsen; Jacqueline M. Vink; Christel M. Middeldorp; Enda M. Byrne; Andrew C. Heath; Pamela A. F. Madden; et al. (Human Genetics, 2014)

The association between pro-inflammatory cytokines, regional cerebral metabolism, and cognitive complaints following adjuvant chemotherapy for breast cancer - K. L. Pomykala; P. A. Ganz; J. E. Bower; L. Kwan; S. A. Castellon; S. Mallam; I. Cheng; R. Ahn; E. C. Breen; M. R. Irwin; D. H. S. Silverman (Brain Imaging and Behavior, 2013)

Regional Distribution of Aerosol Deposition in Rat Lungs Using Magnetic Resonance Imaging - Jessica M. Oakes; Miriam Scadeng; Ellen C. Breen; G. Kim Prisk; Chantal Darquenne (Annals of Biomedical Engineering, 2013)

Extensive conservation of genomic imbalances in canine transmissible venereal tumors (CTVT) detected by microarray-based CGH analysis - Rachael Thomas; Clare Rebbeck; Armand M. Leroi; Austin Burt; Matthew Breen (Chromosome Research, 2009)

Influence of genetic background on tumor karyotypes: Evidence for breed-associated cytogenetic aberrations in canine appendicular osteosarcoma - Rachael Thomas; Huixia J. Wang; Pei-Chien Tsai; Cordelia F. Langford; Susan P. Fosmire; Cristan M. Jubala; David M. Getzy; Gary R. Cutter; Jaime F. Modiano; Matthew Breen (Chromosome Research, 2009)

Electronic tags reveal behaviour of captured and discarded fish - F. C. Neat; M. Breen; R. M. Cook; I. M. Gibb; P. J. Wright (Journal of Fish Biology, 2009)
Internally implanted data storage tags (DST) recording hydrostatic pressure (depth) and temperature in Atlantic cod Gadus morhua were used to track the behaviour of nine individuals during fishing operations. Gadus morhua showed identifiable and characteristic behavioural responses to different capture processes. In a unique observation, one fish survived being discarded and upon return to the seabed exhibited a cessation of activity comparable to observations on stressed fish under laboratory conditions.

MRI-guided Thermal Ablation Therapy: Model and Parameter Estimates to Predict Cell Death from MR Thermometry Images - Michael S. Breen; Miyuki Breen; Kim Butts; Lili Chen; Gerald M. Saidel; David L. Wilson (Annals of Biomedical Engineering, 2007)

Integrated cytogenetic BAC map of the genome of the gray, short-tailed opossum, Monodelphis domestica - S. E. Duke; P. B. Samollow; E. Mauceli; K. Lindblad-Toh; M. Breen (Chromosome Research, 2007)

Watershed Nitrogen and Mercury Geochemical Fluxes Integrate Landscape Factors in Long-term Research Watersheds at Acadia National Park, Maine, USA - J. S. Kahl; S. J. Nelson; I. Fernandez; T. Haines; S. Norton; G. B. Wiersma; G. Jacobson; A. Amirbahman; K. Johnson; M. Schauffler; L. Rustad; K. Tonnessen; et al. (Environmental Monitoring and Assessment, 2007)

Host propagation permits extreme local adaptation in a social parasite of ants - K. Schönrogge; M. G. Gardner; G. W. Elmes; E. K. V. Napper; D. J. Simcox; J. C. Wardlaw; J. Breen; B. Barr; J. J. Knapp; J. A. Pickett; J. A. Thomas (Ecology Letters, 2006)
The Red Data Book hoverfly species Microdon mutabilis is an extreme specialist that parasitises ant societies. The flies are locally adapted to a single host, Formica lemani , more intimately than was thought possible in host–parasite systems. Microdon egg survival plummeted in F. lemani colonies > 3 km away from the natal nest, from c. 96% to 0% to Microdon manipulates the social dynamics of F. lemani by feeding selectively on ant eggs and small larvae, which causes surviving larvae to switch development into queens. Infested colonies rear double the number of new queens, thus propagating the vulnerable local genotype and compensating for damage to the host colonies. The consequences of such extreme host specificity for insect conservation are discussed.

Construction and integration of radiation-hybrid and cytogenetic maps of dog Chromosome X - Helen F. Spriggs; Nigel G. Holmes; Matthew Breen; Panos Deloukas; Cordelia F. Langford; Mark T. Ross; Nigel P. Carter; Maria E. Davis; Catherine Knights; Angela Smith; Christine J. Farr; Linda C. McCarthy; et al. (Mammalian Genome, 2003)

Molecular cytogenetic analysis of a novel high-grade canine T-lymphoblastic lymphoma demonstrating co-expression of CD3 and CD79a cell markers - Rachael Thomas; Ken C. Smith; Rob Gould; Sue M. Gower; Matthew M. Binns; Matthew Breen (Chromosome Research, 2001)

Perceptions of the Forestry and Wildlife Policy by the local communities living in the Maputo Elephant Reserve, Mozambique - Bartolomeu Soto; Simon M. Munthali; Charles Breen (Biodiversity and Conservation, 2001)

An integrated cytogenetic, radiation-hybrid, and comparative map of dog Chromosome 5 - Rachael Thomas; Matthew Breen; Panos Deloukas; Nigel G. Holmes; Matthew M. Binns (Mammalian Genome, 2001)

An index for the management of South African estuaries for juvenile fish recruitment from the marine environment - N. W. Quinn; C. M. Breen; A. K. Whitfield; J. W. Hearne (Fisheries Management and Ecology, 1999)
The release of fresh water from major impoundments to meet the requirements of estuaries has become a recognized need and methodologies to define appropriate release strategies have become an urgent priority in some parts of the world. A recruitment index for juvenile marine fish is presented, based on information relating to the preferred recruitment periods for 27 species, as well as the extent of dependency of these species on estuaries. The status of the estuary mouth (i.e. open or closed) and the longitudinal salinity differences (i.e. the difference between the salinity at the estuary head and the mouth) in the estuary are obtained from a hydrodynamic model of the estuary. The recruitment index integrates this information to provide an indication of potential recruitment (or recruitment opportunity). This index was applied in a case study of the Great Brak Estuary, South Africa, and a distinct decrease in the recruitment index was associated with a reduction in freshwater inflow. In the estuary modelled, annual run‐off could be halved without an appreciable decrease in the fish recruitment index (FRI), but with a potentially sharp decline in fish recruitment thereafter. While the index represented recruitment opportunity rather than actual recruitment, it does at least provide an indication of where ecological risk is likely to increase substantially. Since the index integrates the current understanding with respect to the key processes which regulate recruitment of juvenile marine fish into estuaries, it is suggested that it has the potential to fulfil a vital role in identifying appropriate freshwater release policies for impoundments in South Africa.

Localization and Characterization of Nucleotide Sequences From the Canine Y Chromosome - Michael Olivier; Matthew Breen; Matthew M. Binns; George Lust (Chromosome Research, 1999)

FORUM: Partnership Forum Framework: Participative Framework for Protected Area Outreach - ANDREW K. VENTER; CHARLES M. BREEN (Environmental Management, 1998)

The role of glycoproteins in neural development, function, and disease - Kieran C. Breen; Christine M. Coughlan; Fleur D. Hayes (Molecular Neurobiology, 1998)

International system for cytogenetic nomenclature of the domestic horse: Report of the Third International Committee for the Standardization of the Domestic Horse Karyotype, Davis, CA, USA, 1996 - A. T. Bowling; M. Breen; B. P. Chowdhary; K. Hirota; T. Lear; L. V. Millon; F. A. Ponce de Leon; T. Raudsepp; G. Stranzinger (Chromosome Research, 1997)

Genetical and physical assignments of equine microsatellites—first integration of anchored markers in horse genome mapping - Matthew Breen; Gabriella Lindgren; Matthew M. Binns; Julianne Norman; Zlaka Irvin; Kevin Bell; Kaj Sandberg; Hans Ellegren (Mammalian Genome, 1997)

Identification of Papillomaviruses in Scrapings from Bovine Warts by use of the Polymerase Chain Reaction - N. Bloch; R.H. Sutton; M. Breen; P.B. Spradbrow (Veterinary Research Communications, 1997)